METODE ITERASI BARU YANG OPTIMAL BERORDE EMPAT TANPA TURUNAN KEDUA DAN DINAMIKNYA - Fitria Afri Yanti; Imran M.; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses an iterative metho d to solve a nonlinear equation, which is free from second derivative by approximating a second derivative by a divided difference. Analytically it is shown using the Taylor expansion and geometric series that this iterative metho d has a convergence of order four. Furthermore, numerical comparisons between the prop osed metho d and several well-known iterative methods of order four and free from second derivative are p erformed. By varying the initial guesses, we compare the numb er of iterations obtained by those methods to get an approximated ro ot. In addition, comparisons are also made through basins of attraction of the discussed methods.